Thinking on their feet : the role of knowledge in the work of personal training. - Watermeyer, Amanda Jane (My University, 2013)
Personal training is an occupation which requires service and knowledge work. There have been some studies of personal training that have focused on the service dimension of the work of personal trainers but few on the knowledge work entailed in workplace competence. This study focused on “knowledgeable labour” in the field of personal training. A small sample of apprenticed, trained and educated personal trainers was observed at work with their clients in order to investigate whether different learning pathways lead to differences in the forms of knowledge and ways of knowing they use in their workplace practices. A first level of analysis focused on whether there were noticeable differences in the “practical competence” of the trainers -as manifest in their observable practices with their clients. A second level of analysis, explored whether there were more subtle differences in their practices by focusing on the form and content of their exchanges with their clients, and of their reflections in and on their practice. This level of analysis focused on what the South African National Qualifications framework has referred to as “applied competence’ which is grounded in foundational and reflexive competence and is not reducible to what is manifestly or visible in practical activities. It sought to establish whether there were differences in the applied competence of trainers who have qualified through the different learning pathways. The study found that access to a formal knowledge base, and a related ability to reflect explicitly made a difference to the quality of the knowledge that trainers imparted to their clients, to their decision making in practice, and to the quality of explanations and justifications they offered to their clients. These differences point to the need for vocational qualifications that develop reflective practitioners who are able to build bridges work between the science and the client in their situated practices in their workplaces and therefore think on their feet.
Keywords: Personal training; Competence; Knowledge structure; Knowledge work; SAQA